2006
DOI: 10.1080/10903120500541324
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Prehospital Care Times for Trauma

Abstract: Despite the emphasis on time in the prehospital and trauma literature there has been no national effort to empirically define average prehospital time intervals for trauma patients. We provide points of reference for prehospital intervals so that policymakers can compare individual emergency medical systems to national norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
176
3
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(191 citation statements)
references
References 68 publications
8
176
3
4
Order By: Relevance
“…6 In the case where care is rendered on-scene, better diagnostic and therapeutic expertise is essential in reducing pre-hospital intervals. In this application, we therefore identify additional experience as participation in additional ambulance runs and performance as the total out-of-hospital time for a trauma incident, which is considered a key marker of EMS performance (Brendan G. Carr et al 2006). The importance of getting the patient to definitive care as soon as possible, allowing only for the performance of essential procedures, is widely accepted, as shorter out-of-hospital EMS time intervals represent an important factor in survival (Stan Feero et al 1995).…”
Section: Empirical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In the case where care is rendered on-scene, better diagnostic and therapeutic expertise is essential in reducing pre-hospital intervals. In this application, we therefore identify additional experience as participation in additional ambulance runs and performance as the total out-of-hospital time for a trauma incident, which is considered a key marker of EMS performance (Brendan G. Carr et al 2006). The importance of getting the patient to definitive care as soon as possible, allowing only for the performance of essential procedures, is widely accepted, as shorter out-of-hospital EMS time intervals represent an important factor in survival (Stan Feero et al 1995).…”
Section: Empirical Applicationmentioning
confidence: 99%
“…Using this specification, we find little evidence of transferability across incident types, as estimates of β e M are indistinguishable from zero across all models. This may result from EMS protocols being more well-established for medical events relative to trauma events (Carr et al 2006).…”
mentioning
confidence: 99%
“…The many mountainous and medically isolated areas in Fukushima prefecture sometimes caused extended transportation times. This study showed prehospital times of 48.2±23.6 min, while a US meta-analysis of trauma patients [14] showed prehospital times of 43.17 min in rural areas, 30.97 min suburban areas, and 30.96 min in urban areas. Several studies [15][16][17][18] found that a decrease in prehospital time resulted in improved patient survival.…”
Section: Delay In Prehospital Phasementioning
confidence: 47%
“…This networking idea might be appropriate for other countries. Carr et al [10] found different standards of rescue times at a national level, regarding the scene of trauma. Especially in rural areas, greater time is needed for bringing patients to the right hospital.…”
Section: Discussionmentioning
confidence: 99%
“…One is based on a large physician-staffed vehicle that can carry sufficient equipment and two paramedics to the scene [10]. The other system is called the rendezvous system [10].…”
Section: Emergency Medical Systemsmentioning
confidence: 99%